Industry-Institute Interaction - Pande, K. B. (Journal of Engineering Education Transformations, 1995)
Industry-Institute interaction is one topic which, over the past few years, has been discussed at length at various forums. Both the industry and the institutes have always realised the importance and advantages of the wide ranging interaction.